Fitossíntese e caracterização de nanopartículas de ouro sintetizadas com extrato aquoso de Anacardium occidentale e avaliação do seu efeito antibacteriano - Figueira, Ciro Siqueira (2023)
The use of nanobiotechnology is changing the way in which various types of materials are used. The biosynthesis of nanoparticles is a very simple, effective, and relatively low-cost method compared to other methods of producing metallic nanoparticles (NPs). Their behavior is related to the reaction medium in which they are found, their stability, chemical composition, degree of aggregation, morphology, and size, which is why modulations at the time of synthesis are decisive for their biological activity. Most of the routes traditionally used to produce metal nanoparticles use toxic solvents, which generate waste that is harmful to health and the environment. Studies on NPs have shown that they have high antimicrobial potential, drug delivery, among others. The aim of this study was to develop a sustainable methodology for the synthesis of gold nanoparticles, using an aqueous extract of Anacardium occidentale leaves as a reducing agent, and to evaluate their antimicrobial activity. The gold nanoparticles (AuNPs) were synthesized by oxirreduction, based on a design in which the variable observed was the concentration of the reducing agent. Characterization was carried out using UV-Vis, microscopy, zeta potential, ICP-MS and infrared analyses. Antibacterial activity was tested against Staphylococcus aureus 1117 and Escherichia coli DH5α using the broth microdilution technique, and rapid interaction by shaking, followed by Transmission Electron Microscopy analysis. The lyophilized cashew leaf extract was able to reduce gold as effectively as sodium citrate (the commonly used reducing agent). The concentration of the reducing agent was relevant in determining the characteristics of the nanoparticles. The absorbance peak occurred between 519 and 529nm. Together with this data, the microscopy images confirm the presence of gold nanoparticles with an average size of 13 - 23 nm. From the green synthesis the AuNPs had varied shapes and the zeta potential showed that the AuNPs were stable. ICP-MS analysis showed that the concentration of AuNPs with the green synthesis was higher than with citrate. The gold nanoparticles showed antibacterial potential and were able to inhibit the growth of S. aureus by interacting with the membrane. The plant extract proved to be an excellent alternative for the synthesis of AuNPs, resulting in particles with effective antimicrobial activity in inhibiting S. aureus.